A Spotlight on Chemical Constituents and Pharmacological Activities of Nigella glandulifera Freyn et Sint Seeds - Besma Boubertakh; Xin-Guang Liu; Xiao-Lan Cheng; Ping Li (Journal of Chemistry, 2013)
Plants belonging to the Ranunculaceae family, and particularly their seeds, have been a hot research topic in numerous pharmacognosy laboratories. Nigella glandulifera Freyn et Sint (NG) is one of the promising, but relatively insufficiently studied, plants from this family. In this review, we summarize the recently isolated chemical constituents from the seeds of this plant including alkaloids, flavonol glycosides, isobenzofuranone derivatives, saponins, terpenes, terpenoids, and fatty acids. We put also a spotlight on the recently studied therapeutic potentials of such amazing herb seeds as antidiabetes, melanogenesis inhibition, anticancer, anti-inflammatory, antithrombosis, and antiplatelet aggregation effects. Herein, we illustrate certain properties and potentials via selected examples, and thus we suggest more studies to confirm the therapeutic hypotheses, find out new compounds, and eventually to discover novel properties.